1977
DOI: 10.1088/0029-5515/17/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotron radiation as a diagnostic tool for tokamak plasmas

Abstract: A code has been developed which calculates the cyclotron radiation spectrum emitted by a slab model tokamak plasma in a direction outward along a major radius. The calculation assumes both a thermal and a suprathermal electron component for the plasma, and includes the effects of self-absorption of the radiation by the thermal plasma. Various methods are described by which the cyclotron radiation spectrum can be unfolded to obtain parameters of the electron population. A procedure is described by which the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 2 publications
0
45
0
Order By: Relevance
“…The first measurements of ECE were made in the early 1970s by Costley et al 1 . The potential for using the ECE spectrum to diagnose plasmas was suggested by Engelmann and Curatolo 2 and Celata and Boyd 3 . A review of ECE physics and the diagnostic potential of ECE can be found in Bornatici et al 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The first measurements of ECE were made in the early 1970s by Costley et al 1 . The potential for using the ECE spectrum to diagnose plasmas was suggested by Engelmann and Curatolo 2 and Celata and Boyd 3 . A review of ECE physics and the diagnostic potential of ECE can be found in Bornatici et al 4 .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The first ECE measurements from a tokamak were performed on the CLEO device using a Michelson interferometer and InSb detector 22 with early theoretical studies providing a sound foundation for measurement and interpretation. 23,24 This was rapidly followed by measurements on devices throughout the world. Today, this is a routine technique for obtaining electron temperature profiles using a variety of instrument configurations.…”
Section: I~v! ϭ Vmentioning
confidence: 99%
“…Thus, ECE detection from the high-field side ͑HFS͒ of the resonance is a sensitive diagnostic of high-v Ќ electrons whereas oblique LFS detection targets preferentially high-v ʈ electrons. 71,72 The photon statistics of cyclotron emission being generally far better than those of HXR bremsstrahlung, exploiting ECE for diagnosing suprathermal electrons offers in principle a way to achieve superior time resolution. On the other hand, ECE suffers from the significant complication that the energy and the spatial location of the emitting electrons cannot be determined independently in general.…”
Section: Electron-cyclotron Radiationmentioning
confidence: 99%